Health promotion and aging : practical applications for health professionals - Haber, David, 1944- (Springer Publishing Company, LLC, 2016)
The seventh edition of this classic text champions healthy aging by demonstrating how to prevent or manage disease and make large-scale improvements toward health and wellness in the older adult population. The text synthesizes state-of-the-art research findings--providing convincing evidence that health promotion truly works--with practical, effective strategies. Encompassing important research results that supplant prior recommendations, this new edition provides updated best practices and strategies to ensure the active participation of older adults in all aspects of life. Completely reorganized for ease of use, this textbook features updated demographics and rankings for leading causes of death, new blood pressure screening guidelines and data on obesity and diabetes, updated exercise regimens, older-driver statistics and innovations such as the driverless car, cautions regarding ineffective brain-training programs, and more. Highly practical, the text includes health-promoting tools, resource lists, assessment tools, illustrations, checklists, and tables. Additionally, the book includes key terms and learning objectives at the start of each chapter, along with thought-provoking questions and reflection boxes. An Instructor's Manual and PowerPoint slides are available to facilitate teaching. New to the Seventh Edition: Provides updated blood pressure, cholesterol, Ductal Carcinoma In Situ (DCIS), and lung cancer screening guidelines Presents updates on exercise regimens ranging from yoga to the tango Expands and updates section on emotional regulation and conflict resolution skills with aging Discusses Boomer Entrepreneurism Provides new policy recommendations including student loan debt among older adults Expands gerotechnology and smart home innovations Updates on "Obamacare" and health care delivery recommendations Addresses "Buyer Beware" regarding brain-training programs Expands global aging and LGBT aging content